Multi-Decadal Nutrient Management and Trends in Two Catchments of Lake Okeechobee - Rachael Z. Cooper; Sarina J. Ergas; Mahmood Nachabe (Resources, 2024)
Despite years of efforts to improve water quality, harmful algal blooms remain a chronic phenomenon, with devastating environmental, economic, and social impacts in many regions worldwide. In this study, we assessed the complexity of nutrient pollution attributed to harmful algal blooms in South Florida (USA) by analyzing 20 years of flow and nutrient data within two headwater basins in the Lake Okeechobee (LO) watershed. The study used an established advanced regression method, the Weighted Regression on Time, Discharge, and Season (WRTDS) method, as an analysis framework to examine the impact of nutrient management practices on water quality trends. The WRTDS method produced total phosphorus (TP) and total nitrogen (TN) concentration and flux trends, which were then compared with existing and historic nutrient management records within the basin. Results from this study highlight divergences in progress to improve water quality. Nutrient management practices only had a weak impact on TP and TN flux trends in one of the two basins, where TP flux decreased 2% per year, and TN flux decreased 0.1% per year. TP and TN flux increased in the second basin. Variances of improvement between the two basins are likely attributable to differences in contemporary point source loading and legacy nutrient pools from non-point source inputs 20 years or more before the analysis period. The long-lasting impacts of legacy nutrients also emphasize a need for investments in technologies and practices that can withdraw nutrients from enriched soil and water.